2023
DOI: 10.20870/oeno-one.2023.57.1.7313
|View full text |Cite
|
Sign up to set email alerts
|

Are the characteristics of sparkling wines obtained by the Traditional or Charmat methods quite different from each other?

Abstract: In this study, we performed an analytical and sensorial comparison between sparkling wines produced by the Traditional and Charmat methods using the same base wine, yeast strain, inoculum, and aged on the lees during the same periods. The absence of evident differences in the results of the analyses of physicochemical and volatile compounds was confirmed by the sensory analysis. In general, during the tests, more evaluators could identify differences in the first stages in which sensory analyses were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Very recently, Cisilotto et al [45] compared sparkling wines produced by the Traditional and Charmat methods using the same base wine, yeast strain, inoculum, and aged on the lees during the same periods. The base wine was a blend of Chardonnay (36%), Riesling Italic (30%), and Pinot Noir (34%) vinified in white.…”
Section: The Effect Of the Base Winementioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Cisilotto et al [45] compared sparkling wines produced by the Traditional and Charmat methods using the same base wine, yeast strain, inoculum, and aged on the lees during the same periods. The base wine was a blend of Chardonnay (36%), Riesling Italic (30%), and Pinot Noir (34%) vinified in white.…”
Section: The Effect Of the Base Winementioning
confidence: 99%
“…The differences between the Traditional and Charmat methods in some conditions are not evident to consumers. In a recent paper, previously cited [45], some authors wrote that the method used for the second fermentation is not the determinant of the eventual differences currently associated with sparkling wine produced with the Charmat method and the Traditional method. They observed that more than half of the panelists could not differentiate the samples in all stages.…”
Section: Consumersmentioning
confidence: 99%
“…Sparkling cider can be prepared by different methods: the Champenoise method, Charmat method, Pét-Nat method, and artificial carbonation. The "Méthode Champenoise" requires the secondary fermentation of the base cider in bottles [4], which can lead to the formation of aroma compounds (esters) [5]. However, this method is not economical.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleation of bubbles is restrained by an energy barrier and the supersaturation is weak to overcome it alone. Therefore, in low supersaturated carbon dioxide solutions, including sparkling wines, bubbles nucleate when the pre-existing gas cavities are large enough to overcome the energy barrier to nucleation [13]. The cavities must be large because the curvature of the gas-liquid interface leads to an overpressure inside the gas pocket that is inversely proportional to its radius.…”
Section: Introductionmentioning
confidence: 99%